Slay Your Day: Rahasia Feminine Hygiene Remaja - Irma, Irma; Sallo, Andi Kamal M (Fokus ABDIMAS, 2024)
The socialization of feminine hygiene practices for Generation Z adolescent girls is a crucial step in improving their health and well-being. The "Slay Your Day: The Secret of Adolescent Feminine Hygiene" program was held on August 23, 2024, at SMK Fatimah Mamuju, attended by 50 female students from grades X to XII. Using an interactive lecture method, the speakers from St. Fatimah Mamuju Institute of Health and Business delivered comprehensive materials covering basic menstrual knowledge, the safe use of hygiene products, and the importance of maintaining mental health during menstruation. The participants demonstrated high enthusiasm, actively engaging in discussions, and asking critical questions. This socialization successfully increased the awareness and knowledge of adolescent girls about feminine hygiene, empowering them to take better care of their health. The program addressed the issues of lack of knowledge and access to hygiene products and helped reduce the stigma surrounding menstruation. The participants are expected to become agents of change, spreading knowledge to their peers and families, thereby contributing to improved feminine hygiene practices in their communities.